Novel potential neuroprotective targets for DengZhanXiXin injection in middle cerebral artery occlusion rats recommended by quantitative proteomics and simulated docking - Min Li; Min Li; Linshuang Wang; Haiting An; Xin Li; Xin Li; Yaojing Chen; Yaojing Chen; Dongfeng Wei; Zhanjun Zhang; Zhanjun Zhang (Frontiers in Neuroscience)
Stroke, which leads to death and disability in high proportions globally, is one of the most deleterious neurological diseases. Ischemic stroke (IS) is the major cause of disease attack and accounts for ~70% of all incident stroke cases in China. Up to now, only two therapies for IS were officially approved, which are intravenous administration of recombinant tissue-plasminogen activator (rt-PA) and endovascular mechanical thrombectomy to rapidly recanalize the occluded artery, which both recanalize the occluded artery rapidly to reduce disability, but are limited in a fixed time window. In this study, the therapeutic effect of a traditional Chinese medicine, DengZhanXiXin injection (DZXI), was evaluated on middle cerebral artery occlusion (MCAO) rats at the neurobehavioral and pathophysiological levels through neurological tests, neurohistological staining, proteomic assay, and biological information analysis. We found that DZXI significantly ameliorated the neurological deficit, prevented infarct volume evolution, and protected cortical neural cells from death in ischemia penumbra on MCAO rats. Furthermore, corresponding therapeutic molecular targets were investigated through proteomic analysis of ischemic hemispheres of MCAO rats. One hundred ninety-one differentially expressed proteins involved in response to metal ions, neurofilament bundle assembly, and modulation of chemical synaptic transmission were identified between the MCAO model and DZXI groups after 7 days. DZXI influenced the expression levels of proteins in 13 specific biological functions, with cell signaling and chemical synaptic transmission-associated proteins being most affected. Subsequent molecular docking analysis predicted binding potential between key target proteins and DZXI compounds. The results suggested that DZXI ameliorates neurological deficits by potentially affecting cellular signaling and chemical synaptic transmission physiological processes.